Classification of Romanian Industrial Companies based on the Management Strategic Dimension - Ion VERBONCU; Ovidiu NICOLESCU; Marian NĂSTASE; Ion POPA (Revista de Management Comparat International, 2009)
The interest for strategy expressed within Romanian companies was caused by the fact that the external context has become more and more dynamic and unpredictable, allowing to different factors to exert a more powerful influence over the enterprise than previously expected. Consequently, by elaborating global and specialized strategies the companies try to anticipate and even to shape their direct environment. The analysis performed at this stage is focused on highlighting the main impact elements of endogenous and exogenous variables, conditioning the strategic and cultural dimension of the company related to its managerial and economic performances and, especially, the extent to which the managers understand and use such managerial tools in order to get performances and trigger excellence in management and implicitly excellence in business.